KNOWING THE ASPECTS OF HUMANIZATION OF HEALTH CARE IN THE INTENSIVE THERAPY UNIT INTEGRATIVE REVIEW: INTEGRATIVE REVIEW (CIPEEX, 2022)
INTRODUCTION: HUMANIZATION IS UNDERSTOOD AS A MEASURE THAT SEEKS TO RESCUE HUMAN, PSYCHIC AND SOCIAL RESPECT WITHIN THE HUMAN RELATIONSHIP, WHICH MAY BE NECESSARY FOR THE CORRECTION OF BIOLOGICAL, PHYSIOLOGICAL AND SUBJECTIVE ASPECTS. IT IS FUNDAMENTAL TO ADOPT A PRACTICE IS THE CLIENT AND THE PROFESSIONAL AS PART OF ITS HUMANITARIAN ASSISTANCE AND THE ORGANIZATION OF SUCH CONTEXTS, IT IS A PROCESS THAT AIMS AT AN ETHICAL VIEW OF MUTUAL RESPECT. OBJECTIVES: MAIN: DESCRIBE IN FRONT OF THE SCIENTIFIC LITERATURE AS A HUMANIZATION OF HEALTH IN THE ICU, IMPLICATIONS IN THE DEVELOPMENT OF ACTIONS BY THE NURSING TEAM; SPECIFIC: DESCRIBE HOW A NURSING TEAM ASSOCIATED WITH ITS HEALTH CARE AND A HUMANIZATION TO THE ICU PATIENT. DESCRIBING AS A NURSING TEAM ASSOCIATED WITH ICU PATIENT FAMILY CARE IN THE FACE OF HUMANIZATION. METHODOLOGY: THIS STUDY DEALS WITH AN INTEGRATIVE LITERATURE REVIEW, ACCORDING TO MENDES; SILVEIRA; GALVƑO (2008). RESULTS AND DISCUSSION: A REPORT WAS MADE WITH THE AUTHORS, WITH THE OBJECTIVES OF THE ARTICLE, THE OUTLINE OF THE ARTICLE AND THE RESULTS OF THE RESEARCH. SIX CATEGORIES WERE SELECTED, FOLLOWING THE INCLUSION CRITERIA OF THEIR DOCUMENTS FOR A PROFESSIONAL PERFORMANCE BEFORE THE ICU AND HUMANIZATION PROCESS. FINAL CONSIDERATIONS: THE HUMANIZED CARE MUST BE LIVED WITH GREATER ETHICAL PRACTICALITY, WHERE THE PATIENT IS HEARD AND RESPECTED WITH CARES PERFORMED WITH LOVE, TENDERNESS, RESPECT AND CHARACTERIZED BY A HOLISTIC, REFLECTIVE AND RESPECTFUL LOOK.
Keywords: Humanization. Pediatric ICU. Neonatal ICU. Adult ICU. Nursing.